Improvisations and etudes: an experiment in Active Analysis. Issue 1 (2nd January 2019) - Carnicke, Sharon Marie
ABSTRACT: This essay describes the genesis, process, and results of an experiment on Active Analysis (as developed by Stanislavsky and his protégé Maria Knebel) that was conducted by the author and fifteen actors at the 2018 S Word Symposium at the University of California, Riverside. The experiment was designed to interrogate the boundary between "improvisations" and improvisatory "etudes, " which lie at the heart of Stanislavsky's last, most innovative rehearsal technique. The experimental design juxtaposed improvisations on concrete objects with etudes that adjusted the content of the improvisations to a "map" of the dynamic principles inherent in Active Analysis. This research design was prompted by the prominent director Anatoly Vasiliev, who explained during a master class that "improvisation is freer than an etude, " which engages actors in a process of "mapping the play." This process limits actors' freedom, he added, by placing them within "the confines of that map." Among the valuable findings of the S Word experiment, one result seemed particularly notable. The actors unanimously reported feeling more secure in the etudes than in the improvisations, because the dynamic structure of the map better allowed them to focus on character relationships, whereas the improvisations had demanded that they pay equal, if not more attention to the creation of story.